2013
DOI: 10.1111/etap.12081
|View full text |Cite
|
Sign up to set email alerts
|

Should Small, Young Technology-Based Firms Internalize Transactions in Their Internationalization?

Abstract: Small, young entrepreneurial firms' governance structure across countries has generated an interesting debate in recent years. That is, should these firms internalize or externalize transactions in their internationalization? Existing studies suggest that there are advantages and disadvantages to both structures, but the findings are mixed. This study explores the factors that determine the governance structure of small, young technology-based entrepreneurial firms (SYTEFs). Evidence collected in this study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 71 publications
(170 reference statements)
1
18
0
1
Order By: Relevance
“…The results of Fisher's Permutation test for the differences between LEs and SMEs indicate that the impact is stronger for SMEs. The findings are reasonable because SMEs are less likely to receive loans from banks and financial support from the government, implying that they are more sensitive to policy changes than large firms (Li et al, 2015;Xue et al, 2019). Therefore, these findings support H2.2.…”
Section: Firm Sizesupporting
confidence: 55%
See 1 more Smart Citation
“…The results of Fisher's Permutation test for the differences between LEs and SMEs indicate that the impact is stronger for SMEs. The findings are reasonable because SMEs are less likely to receive loans from banks and financial support from the government, implying that they are more sensitive to policy changes than large firms (Li et al, 2015;Xue et al, 2019). Therefore, these findings support H2.2.…”
Section: Firm Sizesupporting
confidence: 55%
“…In terms of ownership structure, stateowned enterprises (SOEs) are expected to take more social responsibilities and make great contributions to China's economic growth (Jin et al, 2019). Their state-owned nature manifests in sound credit and operation environment (Li et al, 2015), and hence demonstrates different attitudes towards economic policy changes compared to non-state-owned enterprises (non-SOEs).…”
Section: Moderating Effects: Ownership Structurementioning
confidence: 99%
“…In the past decades, studies on BGs have traced their rapid internationalization to either individual‐level or company‐level antecedents (Jones, Coviello, and Tang, ; Li, Qian, and Qian, ). Individual‐level antecedents are associated with entrepreneurs' psychological qualities, and company‐level antecedents are related to organizational capabilities.…”
Section: Individual‐ and Company‐level Antecedentsmentioning
confidence: 99%
“…Also Li, Qian and Qian (2012) confirmed that technological intensity is positively correlated with the early internationalization (born globals). Li, Qian and Qian (2015) proved that radical innovations are positively correlated with internationalization, as small young technology-based entrepreneurial firms (SYTEFs) that "generate radical innovation are more likely to internalize their foreign operations". Chetty and Stangl (2010) confirmed that internationalized businesses with limited network relationships have incremental internationalization and innovation, but those with diverse network relationships exhibit radical internationalization and innovation.…”
Section: Literature Reviewmentioning
confidence: 99%